High feasibility and antileukemic efficacy of fludarabine, cytarabine, and idarubicin (FLAI) induction followed by risk‐oriented consolidation: A critical review of a 10‐year, single‐center experience in younger, non M3 AML patients. Issue 8 (15th June 2016) - Guolo, Fabio; Minetto, Paola; Clavio, Marino; Miglino, Maurizio; Di Grazia, Carmen; Ballerini, Filippo; Pastori, Giordana; Guardo, Daniela; Colombo, Nicoletta; Kunkl, Annalisa; Fugazza, Giuseppina; Rebesco, Barbara; et al.
Abstract : About 105 consecutive acute myeloid leukemia (AML) patients treated with the same induction‐consolidation program between 2004 and 2013 were retrospectively analyzed. Median age was 47 years. The first induction course included fludarabine (Flu) and high‐dose cytarabine (Ara‐C) plus idarubicin (Ida), with or without gemtuzumab‐ozogamicin (GO) 3 mg/m 2 (FLAI‐5). Patients achieving complete remission (CR) received a second course without fludarabine but with higher dose of idarubicin. Patients not achieving CR received an intensified second course. Patients not scheduled for early allogeneic bone marrow transplantation (HSCT) where planned to receive at least two courses of consolidation therapy with Ara‐C. Our double induction strategy significantly differs from described fludarabine‐containing regimens, as patients achieving CR receive a second course without fludarabine, to avoid excess toxicity, and Ara‐C consolidation is administrated at the reduced cumulative dose of 8 g/m 2 per cycle. Toxicity is a major concern in fludarabine containing induction, including the recent Medical Research Council AML15 fludarabine, cytarabine, idaraubicin and G‐CSF (FLAG‐Ida) arm, and, despite higher anti‐leukemic efficacy, only a minority of patients is able to complete the full planned program. In this article, we show that our therapeutic program is generally well tolerated, as most patients were able to receive subsequent therapy at full dose and in a timely manner, with a 30‐day mortality of 4.8%. The omission of fludarabine in the second course did not reduce efficacy, as a CR rate of 83% was achieved and 3‐year disease‐free survival and overall survival (OS) were 49.6% and 50.9%, respectively. Our experience shows that FLAI‐5/Ara‐C + Ida double induction followed by risk‐oriented consolidation therapy can result in good overall outcome with acceptable toxicity. Am. J. Hematol. 91:755–762, 2016. © 2016 Wiley Periodicals, Inc.